Culturally Responsive Assessment and Evaluation Practices in Multilingual Classrooms - Mita Peter; Ria Lopush (Yayasan Azhar Amanaa Yogyakarta, 2025)
This study explores the implementation of culturally responsive assessment and evaluation practices in multilingual classrooms. It aims to examine how educators adapt their assessment strategies to accommodate the cultural and linguistic diversity of their students. The research highlights the importance of making assessments more inclusive and equitable, ensuring that all students have an equal opportunity to demonstrate their learning. Through qualitative methods, including interviews, classroom observations, and document analysis, the study identifies the types of culturally responsive assessments used by teachers, the challenges they face, and the impact of these practices on student engagement and academic performance. The findings suggest that culturally responsive assessments enhance students' motivation, participation, and perceptions of fairness. However, challenges such as inadequate training, limited time, and a lack of institutional support remain. The study concludes that culturally responsive assessment practices have the potential to significantly improve educational outcomes, but require ongoing support and professional development for teachers to be fully effective.